Dietary habits and dental caries among preschool children at the University of the Philippines Child Development Center - De la Cruz, Gloria Ramos
Philippine studies on dental diseases revealed a high prevalence rate of dental caries, especially, in the primary dentition. Epidemiologic and experimental investigations have demonstrated certain foods and consumption patterns to be critical in the etiology of dental caries. However, limited data in local literature have tried to explain the high caries rate in the country. The present study was conducted to determine the relationship of dietary habits and dental caries in preschool children aged 3-6 years old. Dietary habits were defined in terms of the frequency of consumption of meals and frequency of consumption of specific cariogenic foods obtained through a questionnaire and 24-hour food record. Dental caries was measured in terms of the number of decayed, missing and filled teeth (dmft) index. The preschool children were arbitrarily classified into three lots depending on the degree of dental caries. Factors other than diet were also investigated such as socio-economic conditions of the family, nature of drinking water and oral hygiene practices. No relationship was found between dental caries and frequency of meals but caries levels were significantly related to frequency of consumption of some specific foods and food groups. Among the cariogenic foods, consumption of toffees was significantly and positively correlated with the degree of dental caries; while fruit beverages were significantly but negatively related. This difference could be attributed to the greater adhesive properties of toffees while fruit beverages are eliminated more rapidly from the mouth. Dietary pattern based on a one-day recording of food consumed revealed no significant differences in the consumption of the different food groups by the three lots of children. However, past dietary practices, as infant feeding practices and age when child started eating supplementary foods, were related to higher mean caries levels. An increase in dental caries levels was also noted with an increase in level of mother's education. An examination of the other factors suspected to be related to caries indicated that children who drank water with more fluoride and better oral hygiene practices had significantly less number of dmft.